(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
This article explains the need for the development of agro-clusters, its importance and place in the development of society, and the developed areas include measures such as equipping agro-clusters with modern technologies, its spiritual renewal, structural technical technological restructuring.